Smarter workouts the science of exercise made simple - McCall, Pete 1972- (Human Kinetics, 2019)
"Smarter Workouts examines why exercise is important, the basic science of how various types of exercise apply different kinds of stimuli to your body, and which types one should do to help improve health and achieve specific results, providing the tools needed to make exercise an integral part of life"